Thermo Scientific Hardware to Optimize the Transfer of HPLC Methods from the Agilent 1260 Infinity System to the UltiMate 3000 SD and the Vanquish Flex UHPLC system - article Editorial (Разработка и регистрация лекарственных средств)
Purpose of the article: To demonstrate the direct transfer of analytical HPLC methods from an Agilent™ 1260 Infinity system to the UltiMate 3000 platform and the Vanquish platform.This article demonstrates the benefits of the UltiMate 3000 and Vanquish platforms for direct transfer of HPLC methods, as required by the USP.Flexible control of total system volume on Thermo Scientific™ UltiMate™ 3000 systems and Thermo Scientific™ Vanquish™ UHPLC systems simplifies the transfer of analytical HPLC methods.The advanced hardware features of the Thermo Scientific™ Vanquish™ LC system allow flexible adjustment of the total system gradient hold volume to facilitate fine tuning during transfer.Equivalent chromatographic results are obtained with both systems, but improved system resolution and repeatability are provided by the Thermo Scientific™ Vanquish™ System.If detection sensitivity is a critical issue, then Thermo Scientific™ LightPipe™ technology is the optimal solution.